Fish muscle the finest type of energy - Kumar, Manindar; Lakshya, Tanmay; Viraj, Raaz (Advances in Aquaculture and Fisheries Management, 2014)
The proximate biochemical composition and seasonal variation in proteins of small indigenous fish species such as Salmostoma sardinella, Cirrinus reba, Garra mullya, Rasbora daniconius and Puntinus conchonius were analyzed. The proximate composition was found to vary among the species. Protein was estimated in S. sardinella (25.64%), C. reba (24.19 %), G. mullya (28.69%), R. daniconius (32.79%) and P. conchonius (27.10%). The present findings revealed that the highest protein content was recorded in R. daniconius fish. The results indicate that R. daniconius shows more protein content as compared to the other fishes. These results showed that in all these fishes, a good quantity of protein is present just like the commercial fishes, so they can be safely used in food to supplement protein. It also indicates that the proximate composition of fish depends on season and also to a great extent on reaction to size, age, sex, reproducing cycle, breeding season and region of catch.